Use of tangential flow filtration for improving detection of viral adventitious agents in cell substrates. Issue 1 (January 2015) - Furtak, Vyacheslav A.; Dabrazhynetskaya, Alena; Volokhov, Dmitriy V.; Chizhikov, Vladimir
Abstract In this study, we assessed the feasibility of tangential flow filtration (TFF) for primary concentration of viral adventitious agents (AAs) from large volumes of cell substrate-derived samples, such as cell-free Chinese hamster ovary (CHO) culture supernatants (500 mL) and CHO cell lysates (50 mL), prior to virus detection in them by nucleic acid-based methods (i.e., qPCR and massively parallel sequencing (MPS). The study was conducted using the samples spiked with four model DNA viruses (bovine herpesvirus type 4, human adenovirus type 5, simian polyomavirus SV-40, and bovine parvovirus). The results showed that the combined TFF/MPS approach enables reliable detection of as low as 1000 genome equivalents (GE) of each of the four viruses spiked into the cell substrate samples. The final achieved sensitivities of 2 GE/mL for cell culture supernatant and 20 GE/mL for cell lysate make this approach more sensitive than virus-specific PCR and qPCR assays. The study results allowed us to propose that TFF might be useful and valuable method for simple and rapid concentration of potential AAs in cell substrate samples prior to AAs detection by conventional in vivo, in vitro, or molecular methods.